Analisis Manajemen Kurikulum Merdeka Belajar oleh Stakeholders Pendidikan pada Madrasah di Kabupaten Tanah Datar - Fazis, Muhammad; Febrian, Vicky Rizki (Jurnal Manajemen Pendidikan Islam (MANAPI), 2024)
Kurikulum Merdeka Belajar is a new policy from the Indonesian Ministry of Education and Culture, which was conveyed by the Indonesian Minister of Education and Culture, the Advanced Indonesia Cabinet. According to Nadiem, the essence of independent thinking must be instilled in teachers first before being applied to students. Without the translation of basic competencies and curriculum, no learning will occur at the existing teacher competency level. The type of research used in this research is qualitative research with a case study approach. The data collection methods used in the research were observation and interview techniques. The results of this research reveal that: implementing the independent learning curriculum at madrasas in Tanah Datar Regency, of course there are opportunities, challenges, threats and obstacles that occur. Among the forms of opportunity obtained is the support from the head of the madrasah, the curriculum development team at the madrasah in Tanah Datar Regency, teachers and parties involved in implementing the independent learning curriculum, in its implementation there are also several challenges that must be faced, these challenges lie in madrsahs and the readiness of educators as learning leaders. Madrasas in Tanah Datar Regency must be ready in terms of facilities and infrastructure, renewal/innovation, and teachers who do not master technology are required to be able and master technology in order to support the learning process.